"It is the hunter and you are the harpooned dolphin": Memory, Writing, and Medusa—Amos Oz and His Women - Wheatley, Natasha (2010)
This article reads Amos Oz's memoir A Tale of Love and Darkness against the long tradition of encountering Jerusalem in literature. It argues that Oz's impulse to write arises from a troubled relationship with the feminine: his creative act consists in a recurring reflex of repulsion when confronted with women and "their emotions." The psycho-sexual conflation of women, memory and Jerusalem – and especially the need both to flee from and master these female figures and their demands – structures his storytelling in an all too contemporary portrait of Jerusalem as a site of desire, conquest, and death.
Keywords: the feminine; Writing; Death; oedipal; Memory; Jerusalem; Autobiography; Amos Oz